Tolerance and liberalism: Studying government and governance - Rai, Dhananjay (Indian Journal of Public Administration)
The article problematises ipso facto existence of tolerance in liberalism and liberal democracy. The liberalism creates two sets of values. The first set of values encompasses democracy and unity. Tolerance, inter alia, becomes a part of second set of values. The article exhibits the outcome of conflict between the first set of values and the second set of values of liberalism. Besides, tolerance and inequality are not discussed conjointly due to insufficient attention given to the latter. The article discusses inequality question in the backdrop of governance discourse for discerning tolerance. The article suggests that the liberal problematic concerning tolerance can be overcome only by way of democratised polity. - Reproduced.
Keywords: Liberalism; Governance; Public administration